Phenotypic diversity for quantitative and qualitative characters of barley (Hordeum vulgare) accession from Algeria - Warda TAIBI; AMINA BELLETRECHE; MOHAMMED KHARSI; SEMIR BECHIR SUHEIL GAOUAR (Society for Indonesian Biodiversity, 2019)
Abstract. Taibi W, Belletreche A, Kharsi M, Gaouar SBS. 2019. Phenotypic diversity for quantitative and qualitative characters of barley (Hordeum vulgare) accession from Algeria. Biodiversitas 20: 3794-3803. Little is known about the diversity of barley in Algeria. An inventory has been conducted in Algeria (North and South) to collect local accessions of barley (Hordeum vulgare L.). A collection of 34 traditional and exotic accessions of barley was characterized using 12 quantitative and 18 qualitative agro-morphological traits. The phenotypic diversity was determined by the Shannon-Weaver diversity index (H') at different levels (global, by type of barley and varietal name). The H' estimates showed a wide phenotypic variability for different traits with H’ average of 0.74 and 0.53 from quantitative and qualitative characters, respectively. The results of the multiple correspondence analysis and hierarchical clustering showed a clear distinction between the different accessions. The results of this work have revealed a great phenotypic diversity of barley accessions that only partially matches the names of varieties because of the existence of homonyms and synonyms in the names given by farmers. The information gathered from this study could be used in conventional breeding programs and in situ conservation of diversity.